Respuesta :

Answer:

a. f(-1)=12

b. f(2t)=16t²-6t+5

c. f(t-2)=4t²-19t+27

Step-by-step explanation:

For a, b, c, we are given an input. We plug that into f(x) to find our answers.

a.  f(-1)=12

f(-1)=4(-1)²-3(-1)+5

f(-1)=4+3+5

f(-1)=12

-------------------------------------------------------------------------------------------------------------

b. f(2t)=16t²-6t+5

f(2t)=4(2t)²-3(2t)+5

f(2t)=4(4t²)-6t+5

f(2t)=16t²-6t+5

-------------------------------------------------------------------------------------------------------------

c. f(t-2)=4t²-19t+27

f(t-2)=4(t-2)²-3(t-2)+5

f(t-2)=4(t²-4t+4)-3t+6+5

f(t-2)=4t²-16t+16-3t+6+5

f(t-2)=4t²-19t+27